Particles exposures and sarcoidosis - Ghio, Andrew J.; Scott, Spencer A.; Tilley, Stephen L. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Sarcoidosis is a chronic disease characterized by the formation of non-caseating granulomas with the lung being the most frequently involved organ. The current diagnosis of sarcoidosis requires that the etiology be idiopathic with alternative causes of granulomatous disease excluded. The assessment that sarcoidosis has no known cause has been challenged by numerous case reports, case series, and epidemiologic studies supporting associations of this disease with recognized exposures to particles.Objective: The literature is reviewed to test for an association between particle exposures and a diagnosis of pulmonary sarcoidosis.Methods: A systematic review of the literature was performed using PubMed/MEDLINE, Web of Science, and TOXNET.Results: Particles can impact a development of granulomas comparable or identical to those in sarcoidosis patients. Prominent among these particles which participate in a pathogenesis of sarcoidosis are silicas and silicates, metals and metal oxides, and World Trade Center dust.Conclusions: Particle exposure is frequently associated with pulmonary sarcoidosis and should not preclude the diagnosis.